2012
DOI: 10.1159/000338816
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel <b><i>COH1</i></b> Mutations in an Italian Patient with Cohen Syndrome

Abstract: Cohen syndrome (CS) is an autosomal recessive disease caused by mutations in the COH1 gene. It is characterized by intellectual disability, hypotonia, joint hyperlaxity, severe myopia, characteristic facial dysmorphisms and, in some cases, intermittent isolated neutropenia. We investigated an Italian patient with CS together with his family. Genetic analysis disclosed 2 novel mutations: the first is an intronic mutation (c.8697–9A>G) creating a new splice site 8 nucleotides upstream, and the second is a duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Eventually, splicing mutations can disrupt the original splice-sites and generate new ones [ 30 , 31 ], like in the mutations c.4320+4A>G (patient 5) and c.5575-1G>A (patient 8) ( Figure 1 , Table 1 ). In patient 5, an expansion of four nucleotides in exon 19 could be observed that disrupted the reading frame.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, splicing mutations can disrupt the original splice-sites and generate new ones [ 30 , 31 ], like in the mutations c.4320+4A>G (patient 5) and c.5575-1G>A (patient 8) ( Figure 1 , Table 1 ). In patient 5, an expansion of four nucleotides in exon 19 could be observed that disrupted the reading frame.…”
Section: Discussionmentioning
confidence: 99%
“…507,508 Cohen syndrome consists of abnormal facies, cognitive impairment, and retinal dystrophy in association with neutropenia and results from mutations in the VPS13B (vacuolar protein sorting 13 homolog B) gene, which is important for lysosome function. 509 Neutropenia also arises from mutations in the gene encoding the late endosomal/lysosomal adaptor mitogenactivated protein kinase and MTOR activator 2 (LAMTOR2), which is also important for lysosome function. 510 Finally, the syndrome of poikiloderma with neutropenia arises from mutations in the U6 snRNA biogenesis 1 (USB1) gene, which encodes a nuclear RNA processing enzyme.…”
Section: Phagocytic Cell Defectsmentioning
confidence: 99%
“…The majority of them are stop or frameshift mutations with five affecting the same region as in our family. Missense and intronic mutations resulting in aberrant splicing have also been identified . VPS13B is a Golgi‐associated peripheral membrane protein co‐localizing with the cis ‐Golgi matrix protein GM130 .…”
Section: Discussionmentioning
confidence: 99%
“…Missense and intronic mutations resulting in aberrant splicing have also been identified. 3,20 VPS13B is a Golgi-associated peripheral membrane protein co-localizing with the cis-Golgi matrix protein GM130. 8 Two retinitis pigmentosa disease genes, RP2 and RPGR, localize to the Golgi, and depletion of RP2 leads to abnormal Golgi function and protein transport in the photoreceptor.…”
Section: Discussionmentioning
confidence: 99%